GIS Application for Estimating the Current Status of Municipal Solid Waste Management System: Case Study of Chandigarh City, India - Khajuria, A.; Matsui, T.; Machimura, T. (Our Nature, 2012)
The population growth in many urban cities and its urban activities in developing countries have resulted in an increased generation rate of municipal solid waste(MSW), an important issue. In the process of municipal solid waste management (MSWM) system in which, collection activities contributed the most of total cost that is paid for MSW collection activities by city’s citizen; and transport activities are required 60-70% of total cost that is the total expenditures spent on the transport, transfer, disposal and treatment of MSW by city authorities. Hence optimization of routing system, systematization of collection, transport and transfer activities is the important components for an effective MSWM system. This article describes the current problems and the improvement of the management activities in a city of Chandigarh. An integrated MSWM assessment model is proposed and used as a decision support tool for daily efficient operations such as collection/ transport path management, load balancing within vehicles, fuel consumption management by using GIS application. In addition, a simple optimal routing model is proposed to achieve the minimum cost/distance/time efficient collection and transport path for MSWM. DOI: http://dx.doi.org/10.3126/on.v9i1.5729